Synthesis and Antibacterial Activity of Some Chlorosubstituted Isoxazolines - S. Deshmukh, Meghana; P.R. Rajput, P.R.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
Isoxazolines (2a–d) were prepared from 2´-hydroxychalocnedibromides and hydroxylamine hydrochloride in DMSO containing a little piperidine on 2.5 h reflux with 80-85% yield. The compounds (2a–d) were assayed against some gram positive and gram negative bacteria. The results obtained are very interesting.